2nd International Workshop on Evidence-based Technology Enhanced Learning - Vittorini, Pierpaolo.; Gennari, Rosella.; Marenzi, Ivana.; Mascio, Tania Di.; Prieta, Fernando De la. (Advances in Intelligent Systems and Computing,, 2013)
Research on Technology Enhanced Learning (TEL) investigates how information and communication technologies can be designed in order to support pedagogical activities. The Evidence Based Design (EBD) of a system bases its decisions on empirical evidence and effectiveness. The evidence-based TEL workshop (ebTEL) brings together TEL and EBD. The first edition of ebTEL collected contributions in the area of TEL from computer science, artificial intelligence, evidence-based medicine, educational psychology and pedagogy. Like the previous edition, this second edition, ebTEL13, wants to be a forum in which TEL researchers and practitioners alike can discuss innovative evidence-based ideas, projects, and lessons related to TEL. The workshop took place in Salamanca, Spain, on May 22nd-24th 2013.